Strained glass alloy and method of making same

CN122941972APending Publication Date: 2026-10-20XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511226718.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-29
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,现有的宽温域弹性合金存在两大技术瓶颈:其一,不能兼具高强度和大应变以提供高储能的弹性,无法契合高负载、大驱动及小型化应用;其二,弹性不能在超宽温度范围内保持稳定,难以应对极端温度工况的挑战

Benefits of technology

[0049]本发明利用塑性变形强化机制及工艺对相变行为和力学性能的调控,成功制备出具有超宽温域恒弹性的高强高温TiNi基应变玻璃合金。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

A strained glass alloy and its preparation method are disclosed. The preparation method includes the following steps: subjecting a TiNi-based alloy material with martensitic phase transformation characteristics to thermomechanical treatment to suppress the martensitic phase transformation and form a strained glass state. The thermomechanical treatment integrates plastic deformation with heat treatment. By adjusting the degree of plastic deformation and heat treatment parameters, the defect concentration of the material is controlled, transforming the TiNi-based alloy material into a TiNi-based strained glass alloy. This invention utilizes the plastic deformation strengthening mechanism and process to control phase transformation behavior and mechanical properties, successfully preparing a high-strength, high-temperature TiNi-based strained glass alloy with ultra-wide temperature range constant elasticity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of strained glass alloys, and in particular to a strained glass alloy, its preparation method, and the alloy thereof. Background Technology

[0002] Shape memory alloys are an important class of metallic smart materials. They can sense the excitation of external physical fields (temperature, stress, magnetic fields, etc.) and generate corresponding drives to achieve various intelligent properties. Martensitic phase transformation is a common phase transformation behavior in shape memory alloys, and its essence is a spontaneous non-diffusional structural phase transformation. In the martensitic phase transformation, the parent phase lattice undergoes long-range shear and transforms into martensite. Therefore, the lattice strain of martensite is long-range ordered relative to the parent phase, which can be called the long-range ordered state of lattice strain. Since the crystal symmetry of martensite is lower than that of the parent phase, the martensitic phase transformation leads to the formation of many different crystallographic orientations and multi-scale martensitic twin / martensitic domain structures. The size of martensitic twins is mostly in the micrometer range, and their response to stress and temperature leads to functional properties such as shape memory effect, hyperelasticity, and damping effect, which have an important impact on the technological applications of shape memory alloys. Research has also discovered a new material state in shape memory alloy systems—strain glass. During the strain glass transition, there is no change in the average structure, but rather the formation of many randomly distributed nanoscale strain domains, rather than the formation of micrometer-scale martensitic twins. Strain glass alloys with nanoscale strain domains exhibit many functional properties.

[0003] With the rapid development of cutting-edge fields such as space technology, near-Earth planetary development, and new energy vehicles, the demand for wide-temperature-range high-elasticity alloys is becoming increasingly urgent. However, existing wide-temperature-range elastic alloys suffer from two major technical bottlenecks: first, they cannot simultaneously possess high strength and large strain to provide high energy storage elasticity, making them unsuitable for high-load, large-drive, and miniaturized applications; second, their elasticity cannot remain stable over an ultra-wide temperature range, making it difficult to cope with the challenges of extreme temperature conditions. Existing wide-temperature-range strain glass elastics have limited maximum service temperatures, and their elastic limits are far below ideal strength, thus failing to achieve high-strength, large-strain elastic energy storage.

[0004] There is an urgent need in this field to develop high-elasticity alloys with a wide temperature range. Summary of the Invention

[0005] To solve the above-mentioned technical problems, this invention discloses a method for preparing strained glass alloys, comprising the following steps:

[0006] Thermomechanical treatment of TiNi-based alloys exhibiting martensitic phase transformation characteristics can suppress the martensitic phase transformation and form a strained glassy state.

[0007] The thermomechanical treatment combines plastic deformation with heat treatment. By adjusting the degree of plastic deformation and heat treatment parameters, the concentration of material defects is controlled, transforming TiNi-based alloy materials into TiNi-based strain glass alloys.

[0008] Preferred,

[0009] The degree of plastic deformation is not less than the critical degree of plastic deformation required to completely suppress the martensitic phase transformation; and

[0010] The heat treatment parameters are controlled within a range that maintains the material in a strained glass state with a high defect concentration.

[0011] Preferred,

[0012] The thermomechanical treatment is selected from one of the following methods:

[0013] 1) Annealing after cold plastic deformation: First, perform cold plastic deformation at room temperature, then perform annealing; or

[0014] 2) Warm plastic deformation treatment: at temperatures above alloy A f Plastic deformation occurs at a temperature where A... f The temperature indicates the termination temperature of the stabilization martensite reversal transformation.

[0015] Preferred,

[0016] The TiNi-based alloy material is in the form of a plate or wire.

[0017] Preferred,

[0018] When the plate or wire is subjected to thermomechanical treatment,

[0019] The plastic deformation is at least one of cold rolling, warm rolling, or cold drawing, wherein...

[0020] When cold rolling or cold drawing, the heat treatment also includes annealing.

[0021] During warm rolling, the degree of plastic deformation is adjusted; or during cold rolling, the degree of plastic deformation, annealing temperature, and annealing time are adjusted to control the defect concentration, phase transformation behavior, and mechanical properties of the TiNi-based alloy material, so that it exhibits the constant elasticity Elinvar effect over a wide temperature range.

[0022] Preferred,

[0023] The deformation degree of cold rolling is 30% to 85%, the deformation degree of warm rolling is 60% to 93%, and the cross-sectional area shrinkage rate of cold drawing is 50% to 65%, preferably 63%.

[0024] Preferred,

[0025] 1) When the TiNi-based alloy material is Ti 39 Ni 41 Nb 20 For alloy sheets, the parameters for annealing after cold rolling are as follows:

[0026] Annealing temperature range: 723 K - 823 K;

[0027] Annealing time range: 5 min - 60 min;

[0028] 2) When the TiNi-based alloy material is Ti 50 Ni 50 For alloy sheets, the parameters for annealing after cold rolling are as follows:

[0029] Annealing temperature: 523K to 583K;

[0030] Annealing time: Short annealing time not exceeding 3 minutes;

[0031] 3) When the TiNi-based alloy material is Ti 50 Ni 50 For alloy wire, the parameters for annealing after cold drawing are as follows:

[0032] Annealing temperature: 473K to 573K;

[0033] Annealing time: Short annealing time not exceeding 15 minutes.

[0034] Preferred,

[0035] The temperature range is 93 K to 453 K.

[0036] Preferred,

[0037] The elastic limit properties of the TiNi-based strained glass alloy are: strength of 1.5 GPa-2 GPa and recoverable strain of 4.5%-6%.

[0038] The elastic modulus of the TiNi-based strained glass alloy is 33 GPa-54 GPa;

[0039] The elastic energy storage density of the TiNi-based strained glass alloy is 30 J / cm³. 3 -61J / cm 3 .

[0040] Preferred,

[0041] Before thermomechanical treatment, the TiNi-based alloy material plates also undergo the following treatments:

[0042] The initial sheet metal is processed into metal strips using wire electrical discharge machining, followed by mechanical polishing.

[0043] The mechanically polished sample was placed in a quartz tube and sealed, and then subjected to solid solution treatment under argon protection.

[0044] After solution treatment, mechanical polishing is performed again.

[0045] Preferred,

[0046] The solution treatment was carried out under argon protection at a temperature of 1223 K to 1273 K for 3 h, followed by quenching and cooling.

[0047] Furthermore, this invention also discloses a strained glass alloy prepared using any of the methods described above.

[0048] Compared with the prior art, the beneficial effects of this invention are as follows:

[0049] This invention utilizes the plastic deformation strengthening mechanism and process to regulate phase transformation behavior and mechanical properties, successfully preparing a high-strength, high-temperature TiNi-based strained glass alloy with ultrawide temperature range constant elasticity.

[0050] The description provided is merely an overview of the technical solution of this invention. In order to make the technical means of this invention clearer and more understandable, so that those skilled in the art can implement it according to the contents of the specification, and to make the described and other objects, features and advantages of this invention more apparent and understandable, the invention will be described below in conjunction with the accompanying drawings. Attached Figure Description

[0051] Various other advantages and benefits of the present invention will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. In the drawings:

[0052] Figure 1 This is a schematic diagram of the process for preparing TiNi-based strained glass alloys using TiNi alloy plates in one embodiment of the present invention;

[0053] Figure 2 This is a schematic diagram of the process for preparing TiNi-based strained glass alloy from TiNi alloy wire in another embodiment of the present invention;

[0054] Figure 3 In several embodiments of the present invention, Ti with different degrees of cold rolling 39 Ni 41 Nb 20 Schematic diagram of the room temperature mechanical properties of the alloy;

[0055] Figure 4 In another embodiment of the present invention, Ti 39Ni 41 Nb 20 A schematic diagram of the distribution of strain glass-transition strain glass-martensite state in alloy cold-rolled glass after 45% post-annealing.

[0056] Figure 5 In another embodiment of the present invention, CR-45%Ti 39 Ni 41 Nb 20 A schematic diagram of room temperature tensile stress-strain curves of alloys annealed at different temperatures for 15 min, where CR represents cold rolling;

[0057] Figure 6 It is CR-45%Ti 39 Ni 41 Nb 20 A schematic diagram showing the changes in mechanical properties of an alloy after annealing at different temperatures for 15 min, where (a) corresponds to the recovery strain and (b) corresponds to the critical pressure for the martensitic transformation.

[0058] Figure 7 It is CR-45%Ti 39 Ni 41 Nb 20 A schematic diagram of room temperature tensile stress-strain curves for alloy 798 K annealed samples for different durations.

[0059] Figure 8 It is CR-45%Ti 39 Ni 41 Nb 20 A schematic diagram of the changes in mechanical properties of alloy 798 K annealed samples at different times, where (a) corresponds to the critical pressure of martensitic phase transformation and (b) corresponds to the recovery strain.

[0060] Figure 9 In several embodiments of the present invention, CR-45%Ti 39 Ni 41 Nb 20 A schematic diagram showing the study of the wide-temperature-range superelasticity of the alloy by annealing it at (a) 773 K, (b) 798 K and (c) 823 K for 15 min and using variable-temperature tensile stress-strain curves. The samples annealed at (a) 773 K and (b) 798 K are in the strain glass state, and the sample annealed at (c) 823 K is in the martensitic state with a defect degree close to that of strain glass. All three annealed samples can exhibit superelasticity in a wide temperature range from 123 K to 373 K.

[0061] Figure 10 In several embodiments of the present invention, CR-45%Ti 39 Ni 41 Nb 20A schematic diagram of the mechanical properties-temperature dependence of the sample annealed for 15 min, where (a) corresponds to the critical stress-temperature dependence and (b) corresponds to the strain-temperature dependence.

[0062] Figure 11 This is a schematic diagram illustrating the variation of the modulus change coefficient e with the amount of cold rolling plastic deformation ε in another embodiment of the present invention;

[0063] Figure 12 In several embodiments of the present invention, cold rolling followed by annealing at 573 K for 15 hours (STi) is performed. 50 Ni 50 A schematic diagram of the wide-temperature-range linear elasticity of strained glass alloys, where (a) corresponds to CR-45% annealing at 573 K for 15 s, and (b) corresponds to CR-80% annealing at 573 K for 15 s.

[0064] Figure 13 In several embodiments of the present invention, Ti 50 Ni 50 Schematic diagrams of room temperature cold rolling and 423 K warm rolling of the alloy;

[0065] Figure 14 In several embodiments of the present invention, Ti 50 Ni 50 A schematic diagram comparing the results of DSC and room temperature XRD of alloy cold-rolled and 423 K warm-rolled samples at different temperatures, where (a) corresponds to the DSC result at higher temperatures and (b) corresponds to the XRD result at room temperature.

[0066] Figure 15 This is a schematic diagram of the DSC results of Ti50Ni50 alloy before and after 92% warm rolling at 423 K in several embodiments of the present invention, wherein (a) corresponds to the solid solution sample and (b) corresponds to the WR-92% sample; where WR represents warm rolling;

[0067] Figure 16 In several embodiments of the present invention, 92% Ti before and after 423 K temperature rolling. 50 Ni 50 A schematic diagram of the in-situ temperature-varying XRD results of the alloy, where (a) corresponds to the solid solution sample and (b) corresponds to the WR-92% sample;

[0068] Figure 17 In several embodiments of the present invention, 92% Ti is rolled at 423 K. 50 Ni 50 A schematic diagram of frequency dispersion anomalies in strained glass alloys, where (a) corresponds to the storage modulus-temperature curves at different frequencies, and (b) corresponds to the Vogel-Fulcher fitting results.

[0069] Figure 18In another embodiment of the present invention, 92% Ti is rolled at 423 K. 50 Ni 50 A schematic diagram of the ZFC / FC experimental results for strained glass alloys;

[0070] Figure 19 This is a schematic diagram of the in-situ cooled selected area diffraction pattern and dark field image of a WR-92% sample in another embodiment of the present invention.

[0071] Figure 20 In several embodiments of the present invention, warm-rolled Ti 50 Ni 50 A schematic diagram of the wide-temperature-range linear elasticity of strained glass alloys, where (a) corresponds to 83% temperature rolling and (b) corresponds to 92% temperature rolling;

[0072] Figure 21 In another embodiment of the present invention, Ti 50 Ni 50 A schematic diagram of the wide-temperature-range stress-strain curve of the CD-63% 523 K 3 min sample;

[0073] Figure 22 These are examples of different processes inducing Ti in various embodiments of the present invention. 50 Ni 50 A schematic diagram comparing the properties of strained glass alloys, where (a) corresponds to the room temperature stress-strain curve and (b) corresponds to the modulus-temperature dependence curve.

[0074] Figure 23 This is a schematic diagram comparing the performance of the TiNi STG Elinvar alloy prepared by the present invention and the existing Elinvar alloy in several embodiments of the present invention, wherein (a) corresponds to the comparison of recoverable strain-elastic limit and (b) corresponds to the comparison of elastic modulus-elastic limit.

[0075] Figure 24 This is a schematic diagram comparing the elastic energy storage density of the Elinvar alloy prepared by this invention and the classic linear elastic alloy in several embodiments of this invention.

[0076] Figure 25 This is a schematic diagram of the elastic energy storage density-temperature dependence of the TiNi STG Elinvar alloy prepared by this invention and existing Elinvar alloys and spring steel in another embodiment of the present invention.

[0077] Figure 26 This is a schematic diagram comparing the energy density and operating temperature range of the TiNi STG Elinvar alloy prepared by this invention with different energy storage types, in another embodiment of the present invention.

[0078] Figure 27 This is a schematic diagram comparing the energy density and power density of the TiNi STG Elinvar alloy prepared by the present invention with different energy storage types in another embodiment of the present invention, wherein (a) is a comparison of energy density-power density per unit mass, and (b) is a comparison of energy density-power density per unit volume.

[0079] The meanings of the symbols or variables involved in the attached figures are as follows:

[0080] A f Martensite reversal termination temperature

[0081] A f 'Temperature of stabilized martensite reversal to terminate

[0082] A s Martensite reversal onset temperature

[0083] CR (Cold Rolling)

[0084] CD cold drawing

[0085] E Elastic modulus

[0086] M s Martensitic transformation initiation temperature

[0087] M f Martensitic transformation termination temperature

[0088] R resistivity

[0089] T X Crystallization transition temperature

[0090] T0 is the ideal freezing temperature for strained glass transition.

[0091] T g Junction temperature of strained glass transition

[0092] T nd Temperature of nanomartensite domain emergence

[0093] T p-SM The peak temperature corresponding to the martensitic reversal transformation in the DSC results of the stabilized martensitic reversal / quenched samples.

[0094] U e Elastic energy storage density

[0095] WR stands for Warm rolling.

[0096] ΔT induces a decrease in the phase transition temperature of the strained glass state (ΔT = Ms - Tg).

[0097] temperature coefficient of e modulus

[0098] α Coefficient of thermal expansion

[0099] δ is the temperature coefficient of resistance.

[0100] ε is the rate of plastic deformation during rolling.

[0101] ε r Response and Strain

[0102] σ stress

[0103] σ e Elastic limit

[0104] σ y Ultimate strength.

[0105] The present invention will be further explained below with reference to the accompanying drawings and embodiments. Detailed Implementation

[0106] The following will refer to the appendix. Figures 1 to 27 Specific embodiments of the invention will be described in more detail below. While specific embodiments of the invention are shown in the accompanying drawings, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the invention and to fully convey the scope of the invention to those skilled in the art.

[0107] Throughout this specification and claims, the terms "comprising" or "including" are open-ended and should be interpreted as "comprising but not limited to." The subsequent descriptions of preferred embodiments of the invention are intended to illustrate the general principles of the specification and are not intended to limit the scope of the invention. The scope of protection of this invention is determined by the appended claims.

[0108] In one embodiment, the present invention discloses a method for preparing a strained glass alloy, comprising the following steps:

[0109] Thermomechanical treatment of TiNi-based alloys exhibiting martensitic phase transformation characteristics can suppress the martensitic phase transformation and form a strained glassy state.

[0110] The thermomechanical treatment combines plastic deformation with heat treatment. By adjusting the degree of plastic deformation and heat treatment parameters, the concentration of material defects is controlled, transforming TiNi-based alloy materials into TiNi-based strain glass alloys.

[0111] In another embodiment,

[0112] The degree of plastic deformation is not less than the critical degree of plastic deformation required to completely suppress the martensitic phase transformation; and

[0113] The heat treatment parameters are controlled within a range that keeps the material in a strain glass state with high defect concentration.

[0114] In another embodiment,

[0115] The thermomechanical treatment is selected from one of the following modes:

[0116] 1) Annealing treatment after cold plastic deformation: first perform cold plastic deformation at room temperature, then perform annealing treatment; or

[0117] 2) Warm plastic deformation treatment: perform plastic deformation at a temperature higher than the alloy A f temperature, wherein the A f temperature refers to the termination temperature of reverse transformation of stabilized martensite.

[0118] In another embodiment,

[0119] The TiNi-based alloy material is a sheet material or a wire material.

[0120] In another embodiment,

[0121] When performing the thermomechanical treatment on the sheet material or wire material,

[0122] The plastic deformation is at least one of cold rolling, warm rolling or cold drawing, wherein

[0123] During cold rolling or cold drawing, the heat treatment further includes an annealing treatment;

[0124] During warm rolling, the defect concentration, phase transformation behavior and mechanical properties of the TiNi-based alloy material are regulated by adjusting the plastic deformation degree, or during cold rolling, by adjusting the plastic deformation degree, annealing temperature and annealing time, so that the material exhibits a constant-elasticity Elinvar effect in a wide temperature range. The Chinese term for the Elinvar effect is 艾林瓦 effect.

[0125] In another embodiment,

[0126] The deformation degree of cold rolling is 30% to 85%, the deformation degree of warm rolling is 60% to 93%, and the cross-sectional area reduction rate of cold drawing is 50% to 65%, preferably 63%.

[0127] In another embodiment,

[0128] 1) When the TiNi-based alloy material is Ti 39 Ni 41 Nb 20 alloy sheet material, the parameters of the annealing treatment after cold rolling are:

[0129] Annealing temperature range: 723 K - 823 K;

[0130] Annealing time range: 5 min - 60 min;

[0131] 2) When the TiNi-based alloy material is Ti 50 Ni 50 For alloy sheets, the parameters for annealing after cold rolling are as follows:

[0132] Annealing temperature: 523K to 583K;

[0133] Annealing time: Short annealing time not exceeding 3 minutes;

[0134] For the above 2), preferably,

[0135] The annealing temperature was 573K and the annealing time was 15s.

[0136] 3) When the TiNi-based alloy material is Ti 50 Ni 50 For alloy wire, the parameters for annealing after cold drawing are as follows:

[0137] Annealing temperature: 473K to 573K;

[0138] Annealing time: Short annealing time not exceeding 15 minutes.

[0139] Regarding 3) above, preferably,

[0140] The annealing temperature was 523K and the annealing time was 3 minutes.

[0141] In another embodiment,

[0142] The temperature range is 93 K to 453 K.

[0143] In another embodiment,

[0144] The elastic limit properties of the TiNi-based strained glass alloy are: strength of 1.5 GPa-2 GPa and recoverable strain of 4.5%-6%.

[0145] The elastic modulus of the TiNi-based strained glass alloy is 33 GPa-54 GPa;

[0146] The elastic energy storage density of the TiNi-based strained glass alloy is 30 J / cm³. 3 -61J / cm 3 .

[0147] In another embodiment,

[0148] Before thermomechanical treatment, the TiNi-based alloy material plates also undergo the following treatments:

[0149] The initial sheet metal is processed into metal strips using wire electrical discharge machining, followed by mechanical polishing.

[0150] The mechanically polished sample was placed in a quartz tube and sealed, and then subjected to solid solution treatment under argon protection.

[0151] After solution treatment, mechanical polishing is performed again.

[0152] In another embodiment,

[0153] The solution treatment was carried out under argon protection at a temperature of 1223 K to 1273 K for 3 h, followed by quenching and cooling.

[0154] In another embodiment, the present invention discloses a method for preparing a strained glass alloy, comprising the following steps:

[0155] Provide TiNi-based alloy materials, wherein the materials are in the form of plates or wires;

[0156] The sheet or wire is subjected to thermomechanical treatment, which includes a combination of plastic deformation and heat treatment, wherein:

[0157] The plastic deformation is at least one of cold rolling, warm rolling, or cold drawing, wherein the degree of deformation in cold rolling is 30% to 85%, the degree of deformation in warm rolling is 60% to 93%, and the cross-sectional area shrinkage rate in cold drawing is 50% to 65%, preferably 63%.

[0158] The heat treatment includes annealing, with an annealing temperature of 523 K to 823 K and an annealing time of 15 s to 60 min;

[0159] The solid solution treatment is carried out under argon protection, and the temperature of the solid solution treatment is the single-phase temperature (e.g., 1223K to 1273K), the holding time is 3 h, and then quenching and cooling are performed.

[0160] By adjusting the degree of plastic deformation, annealing temperature, and annealing time, the defect concentration, phase transformation behavior, and mechanical properties of the TiNi-based alloy can be controlled, enabling it to exhibit constant elasticity (Elinvar effect) and superelasticity in a wide temperature range from 93 K to 453 K.

[0161] In another embodiment,

[0162] The TiNi-based alloy material has a composition of Ti. 39 Ni 41 Nb 20 or Ti 50 Ni 50 The plate sample was prepared by the following steps:

[0163] Machining: The initial sheet metal is machined into metal strips using wire electrical discharge machining, followed by mechanical polishing;

[0164] Sealing process: The polished sample is placed in a quartz tube and sealed, and then subjected to solid solution treatment under argon protection;

[0165] Plastic deformation:

[0166] If cold rolling is used, the sample is rolled at room temperature to a deformation of 30% to 85%, and then annealed.

[0167] If it is warm rolling, roll the sample at a temperature of 423 K to 453 K until the deformation is 60% to 93%, without annealing;

[0168] Acid pickling and polishing: The treated sample is acid-washed and polished to remove the surface oxide layer and oil stains.

[0169] In another embodiment,

[0170] The composition of the TiNi-based alloy is Ti 50 Ni 50 The filament sample was prepared using the following steps:

[0171] Cut the initial cold-drawn wire to the required length;

[0172] Sealing process: The wire is placed in a quartz tube and sealed, and then subjected to solution treatment under argon protection;

[0173] Annealing treatment: The wire is annealed at a temperature of 523 K to 823 K for 15 s to 60 min, followed by acid pickling and polishing.

[0174] In another embodiment, the present invention discloses a method for preparing a strained glass alloy, comprising the following steps:

[0175] Plastic deformation treatment: The TiNi-based alloy is subjected to plastic deformation processing, which includes at least one of cold rolling, warm rolling or cold drawing, with a deformation amount of 30% to 93%;

[0176] Heat treatment control: Heat treatment is performed after or during plastic deformation. The heat treatment includes annealing, with an annealing temperature of 423 K to 798 K and an annealing time of 15 s to 60 min.

[0177] By controlling the combination of plastic deformation degree and heat treatment parameters, the alloy can form a strained glass state with controllable defect concentration, thus obtaining a strained glass alloy with constant elastic modulus (Elinvar effect) in the temperature range of 93 K to 453 K.

[0178] In another embodiment,

[0179] The plastic deformation process is cold rolling, with a deformation amount of 30% to 85%.

[0180] The heat treatment is an annealing treatment after cold rolling, with an annealing temperature of 573 K to 798 K and an annealing time of 15 s to 30 min.

[0181] In another embodiment,

[0182] The cold rolling deformation is 45%, the annealing temperature is 723 K to 798 K, and the annealing time is 15 min;

[0183] The critical stress of the obtained strain glass alloy is 700 MPa to 1100 MPa, and the recovery strain is 3.6% to 6%.

[0184] In another embodiment,

[0185] The plastic deformation process is warm rolling, with a rolling temperature of 423 K and a deformation amount of 60% to 93%.

[0186] The heat treatment is completed simultaneously during the warm rolling process, without the need for an additional annealing step.

[0187] In another embodiment,

[0188] The warm rolling deformation is 92%;

[0189] The resulting strained glass alloy has an elastic modulus of 33 GPa to 44 GPa, a recovery strain of 4.5%, and a strength of 2 GPa.

[0190] In another embodiment,

[0191] The plastic deformation process is cold drawing, with a cross-sectional area shrinkage rate of 63%.

[0192] The heat treatment is an annealing treatment after cold drawing, with an annealing temperature of 523 K and an annealing time of 3 min;

[0193] The resulting strained glass alloy has a recovery strain of 6%, a strength of 2 GPa, and an elastic modulus of 33 GPa.

[0194] To facilitate understanding of the embodiments of the present invention, the following will provide further explanation and description with reference to the accompanying drawings and several more specific embodiments, and the accompanying drawings do not constitute a limitation on the embodiments of the present invention.

[0195] In another embodiment, the method for preparing a TiNi-based strained glass alloy from a TiNi-based alloy material plate-like initial sample is as follows: Figure 1As shown, it includes three main steps: 1) machining, 2) polishing, and 3) heat treatment.

[0196] If prepared according to the cold rolling process, the initial sample is sequentially subjected to wire electrical discharge cutting, mechanical polishing, tube sealing, solution treatment, mechanical polishing again, cold rolling, annealing, wire electrical discharge cutting, pickling and polishing, and then tested and characterized to verify its performance.

[0197] If prepared using the warm rolling process, the alloy material undergoes electrical discharge wire cutting, mechanical polishing, tube sealing, solution treatment, further mechanical polishing, warm rolling (no annealing is required after warm rolling), electrical discharge wire cutting, pickling and polishing, and then testing and characterization to verify its performance.

[0198] in:

[0199] 1) Machining

[0200] Electrical discharge wire cutting: A pulsed voltage is applied between a molybdenum wire and a sheet metal to generate instantaneous high temperature for cutting. The first cut is to process the initial sheet metal into strips of titanium-nickel based metal of varying thicknesses, with a length of ~200 mm and a width equal to the initial sheet metal thickness, to facilitate subsequent rolling and plastic deformation; the second cut is used to cut the rolled sample into a specific shape suitable for testing and characterization.

[0201] Rolling: A TiNi-based metal strip is placed between rotating rolls, and the upper roll is slowly pressed down to induce plastic deformation in the metal strip. This invention employs two rolling methods: cold rolling (CR) and warm rolling (WR). Cold rolling is performed directly at room temperature, while warm rolling involves holding the metal strip in a muffle furnace for a period of time before each rolling pass, and then quickly feeding the sample between the rolls for rolling.

[0202] 2) Polishing

[0203] Mechanical polishing: To avoid the interference of sample surface defects on performance testing or characterization results, after wire electrical discharge machining or solution treatment, large metal samples should be polished by using SiC sandpaper with a fineness ranging from low to high to remove the oxide layer on the sample surface and ensure that the sample surface is smooth and flat.

[0204] Acid pickling and polishing: For small and irregularly shaped samples used for testing or characterization, acid pickling and polishing are used to remove the oxide layer and oil from the sample surface. The pickling time should be controlled within 30 seconds to ensure that the acid solution does not cause acid etching marks, pitting deformation, or hydrogen evolution problems on the sample surface.

[0205] 3) Heat treatment

[0206] Sealing process: To avoid oxidation caused by the alloy reacting with oxygen at high temperatures, all heat treatment processes involved in this invention are carried out in a quartz tube protected by argon gas.

[0207] Solution treatment: After sealing the TiNi-based alloy material, keep it at the corresponding single-phase temperature (1273 K for TiNi alloy and 1223 K for TiNiNb alloy) for a period of time (e.g., 3 h, to avoid the precipitation of harmful phases), take it out and put it in water, and quickly crush the quartz tube for quenching.

[0208] Heat treatment: The sealed alloy is placed in muffle furnaces at different temperatures for heat treatment.

[0209] Compared to the above embodiments, in another embodiment, for the TiNi-based alloy wire samples, since the initial state is cold-drawn wire, it is only necessary to cut it to the required length, seal it in a tube, and then perform annealing treatments of different degrees before testing and characterization to verify its performance. See [link to relevant documentation]. Figure 2 .

[0210] In another embodiment,

[0211] This invention utilizes Ti with a low Ms (i.e., martensitic transformation initiation temperature, also known as the martensitic phase transformation start temperature). 39 Ni 41 Nb 20 Alloys and high Ms Ti 50 Ni 50 Taking alloys as the research object, thermomechanical treatment processes were used to reduce the defect concentration of the alloys. The phase transformation behavior and wide-temperature-range hyperelastic changes were studied, specifically:

[0212] See Figure 3 Based on Ti 39 Ni 41 Nb 20 By adjusting the defect concentration of alloys through thermomechanical treatment, a series of strain glass alloys with significant stress-induced martensitic phase transformation and nonlinear stress-strain curves were prepared. Critical cold-rolling degree strain glass (CR-30% Ti) was also developed. 39 Ni 41 Nb 20 The defect concentration in the alloy is low, and its phase transformation behavior is greatly affected by the annealing process. Secondly, with the increase of cold rolling degree, the material exhibits a significant work hardening effect, and its fracture strength increases from 1.1 GPa for CR-0% sample to 1.5 GPa for CR-45% sample.

[0213] To systematically demonstrate the influence of different annealing processes on the phase transformation behavior of low-freezing-temperature strained glasses, a CR-45% Ti phase transition glass model was constructed based on the characteristic differences between strained glass (no obvious thermal effect), transition-state strained glass (no obvious exothermic phenomenon when cooling down, but obvious endothermic valley when heating up), and martensite (with obvious exothermic peaks and endothermic valleys). 39 Ni 41 Nb 20 The multiphase state distribution diagram of the alloy after annealing is as follows: Figure 4 It can be seen that the effect of annealing is the opposite of that of plastic deformation, reducing the degree of dislocation defects in cold-rolled samples through dissolution of dislocations and growth of grains. As the degree of annealing increases, that is, the annealing temperature or annealing time increases, the degree of defects in the samples continuously decreases, gradually transforming from a high-defect strained glass alloy after cold rolling into a transition strained glass state with fewer defects and then into a martensitic state.

[0214] Furthermore, such as Figure 5 As shown, to obtain higher strength, a cold-rolled grade of 45% (CR-45%) Ti with the highest initial strength is selected. 39 Ni 41 Nb 20 Using alloys as the research object, this invention systematically studied the effect of annealing at different annealing temperatures for 15 min on their room temperature tensile stress-strain curves through multiple embodiments. Samples annealed at ≤ 798 K were in the strain glass state, and samples annealed at 823 K were in the martensitic state.

[0215] (1) For the unannealed cold-rolled sample, due to the suppression of martensitic phase transformation by a large number of dislocations, no stress-induced martensitic plateau appears even after stretching to the elastic limit. After multiple mechanical trainings, the residual strain is close to zero, at which point it exhibits stable quasi-linear hyperelasticity, with a recovery strain of 3.6% and a strength exceeding 1.3 GPa.

[0216] (2) Annealing at 723 K caused a sloping stress plateau in the initial loading and unloading stress-strain curve, exhibiting a "flag"-shaped hyperelastic characteristic similar to that of traditional TiNi alloys. This indicates that the strain glass alloy underwent a transformation from strain glass to long-range martensite under stress. After mechanical training, the stress-strain cycle of the sample became a "willow leaf"-shaped hyperelasticity, somewhere between linear and "flag"-shaped, with its recovery strain increasing to ~6%. Figure 6 As shown in (a). However, with the increase of annealing temperature, the stress-induced martensitic plateau becomes more pronounced, and the critical stress for the strained glass to martensitic phase transformation gradually decreases from 1100 MPa to 700 MPa, as shown in (a). Figure 6 As shown in (b). The recovery strain initially remained at ~6%, and then continued to decrease after the annealing temperature exceeded 773 K.

[0217] (3) When the sample transforms into the martensitic state (823 K annealed sample), it can still exhibit a similar stress-strain curve. This is because the degree of defects in the martensitic state is slightly less than that of the strain glass alloy annealed at 798 K, and it can still retain part of the parent phase structure at room temperature, so it can undergo stress-induced martensitic phase transformation.

[0218] Furthermore, in another embodiment,

[0219] Figure 7 The room temperature tensile stress-strain curves of the alloy after annealing at 798 K for different durations are illustrated. When the annealing time is ≤30 min, the sample is in the strain glass state, while the sample annealed for 60 min is in the transition strain glass state. Figure 7 It can be known that:

[0220] (1) All annealed samples exhibited similar stress-strain curves: significant stress plateaus appeared during the initial loading process, corresponding to the stress-induced martensitic phase transformation process; after mechanical training, their hyperelastic behavior stabilized into a "willow leaf" shape.

[0221] (2) Due to the high annealing temperature, the samples annealed for 5 minutes exhibited a clear stress plateau. Moreover, with the increase of annealing time, the critical stress for stress-induced martensitic transformation did not change much, remaining between 700 MPa and 800 MPa. Figure 8 As shown in (a). However, the recovery strain first increases to 4%, and then slowly decreases, as... Figure 8 As shown in (b).

[0222] In summary, this invention can effectively regulate the volumetric properties of Ti by adjusting the thermomechanical processing technology. 39 Ni 41 Nb 20 The defect degree, phase transformation behavior and hyperelastic behavior of strained glass alloys can be controlled.

[0223] In another embodiment, to further investigate the impact of thermomechanical processing on wide-temperature-range performance, CR-45%Ti was selected. 39 Ni 41 Nb 20 The alloy was annealed at 773 K, 798 K, and 823 K for 15 min, and its wide-temperature-range hyperelasticity was studied by varying-temperature tensile stress-strain curves. Figure 9 As shown, the samples annealed at 773 K and 798 K are in the strained glass state, while the sample annealed at 823 K is in the martensitic state with a defect level close to that of strained glass. All three annealed samples can exhibit superelasticity in a wide temperature range from 123 K to 373 K.

[0224] Furthermore, the critical stress for stress-induced martensitic phase transformation was determined using the tangent method, and its temperature dependence curve is shown below. Figure 10 As shown in (a), the corresponding Figure 10 Figure (b) illustrates the strain-temperature dependence of the sample over a wide temperature range. To avoid the influence of dislocations reintroduced during mechanical training on the hyperelasticity, only a single loading-unloading cycle was performed. The testing sequence was from high temperature to low temperature sequentially. Before each test reached the target temperature, the sample was first heated to the highest temperature of 373 K to avoid the influence of incomplete phase transitions on the sample properties.

[0225] (1) For the 773 K annealed strained glass alloy, its hyperelasticity exhibits a stress plateau corresponding to the martensitic phase transformation at higher temperatures. As the temperature decreases, the critical stress gradually decreases. When the temperature drops to 123 K, the characteristics of stress-induced martensitic phase transformation disappear, and the hyperelasticity transforms into quasi-linearity. For the 798 K annealed strained glass alloy, although the "flag"-shaped hyperelasticity gradually deforms and transforms into a "willow leaf"-shaped hyperelasticity at low temperatures, the stress plateau of stress-induced martensitic phase transformation can still be observed, and the critical stress also gradually decreases as the temperature decreases. For the 823 K annealed martensitic alloy, since the degree of annealing of this sample is close to that of the 798 K annealed strained glass alloy, the two exhibit similar wide-temperature-range hyperelasticity, but the critical stress and recovery strain are both lower than those of the 798 K annealed sample.

[0226] (2) Compared with the 773 K annealed sample, the hyperelastic curve of the 798 K annealed strain glass alloy, which has a higher degree of annealing, tends to remain in a state with a stress plateau, that is, it is more likely to undergo stress-induced martensitic transformation. In addition, as the annealing temperature increases, the critical stress for inducing martensitic transformation decreases.

[0227] (3) As the temperature decreases, the critical stress for inducing martensitic transformation decreases continuously, and the recovery strain also gradually decreases.

[0228] In summary, this invention utilizes Ti 39 Ni 41 Nb 20 By adjusting the thermomechanical treatment process of the alloy, including the degree of cold rolling deformation, annealing temperature and annealing time, strained glass alloys with different hyperelastic behaviors were prepared.

[0229] In another embodiment, in order to prepare a high-strength, high-temperature TiNi strained glass wide-temperature-range hyperelastic alloy using plates and wires, and to obtain a constant-elastic strained glass alloy with excellent temperature stability, this invention explores a high-strength, high-temperature TiNi-based strained glass alloy with wide-temperature-range constant elasticity by adjusting the plastic deformation and annealing processes. Among these,

[0230] like Figure 11As shown, for low-grade cold-rolled samples, e > 17 × 10 -4 / K -1 This further illustrates that martensitic alloys with low defect levels exhibit significant modulus fluctuations. As the degree of cold rolling increases towards the strained glass state, e gradually decreases to ~7×10⁻⁶. -4 / K -1 This indicates that the modulus becomes less sensitive to temperature changes at this point, exhibiting a certain Elinvar effect, which confirms the successful preparation of Elinvar alloys through plastic deformation-induced strain glass. Figure 11 The modulus change coefficient e can be obtained by 1 Hz dynamic small strain DMA test.

[0231] It should be noted that, due to the oriented microstructure generated during the initial rolling process, the modulus of samples varies to different degrees depending on the angle between the rolling directions, causing an abnormal increase in e when the rolling degree increases from 0% to 10%. To eliminate this effect, this invention selects samples parallel to the rolling direction. As the rolling degree increases, the orientation differences caused by the microstructure gradually decrease.

[0232] See further Figure 12 It illustrates Ti annealed at 573 K for 15 s after cold rolling. 50 Ni 50 The wide-temperature-range linear elasticity of strained glass alloys. The CR-45% 573 K 15 s and CR-80% 573 K 15 s samples represent the critical and ultimate cold-rolling degrees of the strained glass alloys, respectively. As shown in the figure:

[0233] (1) Attributable to its high freezing temperature T g Samples with different rolling degrees all exhibited quasi-linear stress-strain curves of ~3.7% within an ultra-wide temperature range of 93 K to 453 K. This indicates that both samples belong to strained glass alloys with high defect levels and cannot undergo strained glass-martensite transformation under stress.

[0234] (2) Due to the strengthening effect of plastic deformation, the CR-45% strain glass alloy has a high strength of ~1.5 GPa. After further increasing the degree of cold rolling to 80%, the sample exhibits an ultra-high strength of 2 GPa.

[0235] (3) Due to the low degree of defects, the low degree of cold rolling of the sample results in a weak suppression of martensitic phase transformation, and therefore the stress-strain curve has a slight curvature. The high degree of cold rolling of the sample provides extremely stable linear elasticity across the entire temperature range, exhibiting the large strain and high strength Elinvar effect.

[0236] (4) The superelastic stress hysteresis of martensitic alloys originates from the nucleation of martensitic domains and the movement of domain walls. For high-defect strain glass alloys that are linearly elastic, long-range martensitic domains will not be formed, and the movement of domain walls contributes little to the hysteresis. However, nano-martensitic domains that exist over a wide temperature range can be exempted from nucleation, so the stress hysteresis is extremely small.

[0237] Furthermore, such as Figure 13 As shown, in addition to cold rolling plastic deformation, this invention can also utilize a warm rolling process above room temperature to deform shape memory alloys under a higher temperature parent phase. In M f Below, Ti 50 Ni 50 The alloy is in the martensitic state, and rolling at this temperature will produce stabilized martensite, such as room temperature cold rolling; while in A... f Above, Ti 50 Ni 50 The alloy is in the parent phase state, and rolling at this temperature can avoid the formation of stabilized martensite, as explained later in conjunction with 423K warm rolling. Besides the different phase composition after plastic deformation, Ti... 50 Ni 50 The effects of cold rolling and warm rolling on the mechanical properties of alloys, such as strength, recoverable strain, and elastic modulus, are different.

[0238] Furthermore, Figure 14 This indicates Ti 50 Ni 50 Comparison of DSC and room temperature XRD of alloys at different degrees of room temperature cold rolling and 423 K warm rolling, among which,

[0239] like Figure 14 As shown in (a), since plastic deformation occurs in the parent phase, warm rolling at 423 K does not produce stabilized martensite. With increasing rolling degree, the endothermic valley corresponding to the normal martensitic transformation in the DSC results gradually widens and its intensity gradually decreases, indicating that both cold rolling and warm rolling plastic deformation inhibit the martensitic transformation. When the rolling degree is 40%, the endothermic peak corresponding to the normal martensitic transformation in the WR-40% sample is more significant than that in the CR-40% sample, indicating that warm rolling introduces a lower concentration of dislocation defects at the same rolling degree, resulting in weaker inhibition of the martensitic transformation compared to cold rolling. This difference is also reflected in the critical plastic deformation degree for martensitic-strained glass: when the cold rolling degree reaches ~40%, the martensitic transformation is completely inhibited, while warm rolling needs to reach ~83% to achieve the same effect.

[0240] like Figure 14As shown in (b), since rolling at 423 K does not produce stabilized martensite, when the critical rolling temperature reaches ~83%, the WR-83% and WR-92% samples only exhibit the B2 parent phase structure at room temperature. However, the cold-rolled samples show obvious stable martensite characteristics, which require further slight annealing to induce a reverse phase transformation in order to remove them.

[0241] and Figure 14 Similar to the DSC results in (a), when the rolling degree is 40%, the B2 parent phase (strained glass phase) is more dominant in the room temperature XRD of the CR-40% sample compared to the WR-40% sample. This indicates that cold rolling introduces a higher degree of dislocation defects at the same rolling degree, making it easier to induce a strained glass state. For samples with a high rolling degree, the CR-80% cold-rolled sample has more amorphous phases, thus reducing the proportion of crystalline phases. Therefore, the XRD diffraction peak intensity is lower, but the diffraction peaks corresponding to the stabilized martensite can still be observed. (See...) Figure 14 The arrow in (b) points to the location. Because of the higher plastic deformation temperature, the warm-rolled samples produce less amorphous phase during plastic deformation. Therefore, the macroscopic structure of the high-rolling-degree warm-rolled samples (WR-83% and WR-92%) still shows a clear B2 structure, i.e. strained glass state, which is consistent with the DSC results.

[0242] Furthermore, in another embodiment, Figure 15 and Figure 16 This illustrates a 423 K temperature rolled 92% Ti steel. 50 Ni 50 Evidence for the macroscopic structural invariance of strained glass alloys, among which,

[0243] Figure 15 (a) and (b) show Ti before and after warm rolling. 50 Ni 50 The DSC results for the heating and cooling of the alloy are similar to those for light annealing after cold rolling, Ti 50 Ni 50 After the alloy was warm rolled to 92%, the endothermic and exothermic peaks corresponding to the martensitic phase transformation in the DSC completely disappeared, indicating that the martensitic phase transformation was completely suppressed.

[0244] Figure 16 (a) and (b) show Ti before and after warm rolling. 50 Ni 50 In-situ cooling XRD results for the alloy, for Ti 50 Ni 50 Martensitic alloys, when cooled to 323 K (< M... sAt ~344 K, the sample rapidly undergoes a martensitic phase transformation, and its macroscopic structure changes from the B2 parent phase structure to the B19′ martensitic structure accordingly; while the WR-92% alloy remains in the B2 parent phase structure, indicating that its macroscopic structure remains unchanged throughout the entire test temperature range.

[0245] Furthermore, in another embodiment, Figure 17 The DMA results are for the WR-92% strained glass alloy.

[0246] Figure 17 (a) illustrates the minimum point T of the modulus-temperature curves of the WR-92% sample at different frequencies. g There is diffusion, and T g The frequency dispersion conforms to the Vogel-Fulcher relationship. After fitting, its ideal freezing temperature T0 ~ 315 K, as shown... Figure 17 As shown in (b), it reaches the highest level reported to date for strained glass alloys. The freezing temperature T of the strained glass... g Or T0 depends on the phase transformation temperature of the original martensite and the defect form adopted. Unlike room temperature cold rolling, warm rolling has a higher plastic deformation temperature, and the nano-martensite of the induced strain glass alloy can exist at a higher temperature. Therefore, compared with Ti 50 Ni 50 Strained glass alloys (T0 ~ 290 K) induced by slight annealing after cold rolling, with WR-92% samples having a slightly higher T0.

[0247] Furthermore, Figure 18 The ZFC / FC experimental results are for WR-92% TiNi-based strained glass alloys. Similar to strained glass alloys induced by slight annealing after cold rolling, the ZFC and FC curves of the WR-92% sample separate at low temperatures but coincide at high temperatures, showing no characteristics corresponding to martensitic phase transformation. Furthermore, the peak value of ZFC corresponds to the freezing temperature T of the strained glass transition. g ~ 315K, which is related to Figure 17 The results from DMA are consistent.

[0248] Furthermore, Figure 19 The gradient cooling of the WR-92% sample from 373 K (much greater than T0), 315 K (approximately equal to T0), 223 K (less than T0) to 123 K (much less than T0) is illustrated along

[111] . B2 Selected area diffraction patterns and corresponding dark-field images taken along the zone axis (Note: overlay) Figure 19 (Photo taken in the middle circle). Similar to strained glass induced by slight annealing after cold rolling, the WR-92% sample contains 1 / 2(110) of the B19′ nanodomains. B2Superlattice diffraction spots. As the temperature decreases, the superlattice diffraction spots gradually become sharper and brighter, and the corresponding white areas corresponding to the nanomartensite domains in the dark field image gradually increase, indicating that the randomly distributed nanomartensite domains on the B2 parent phase gradually increase and grow as the temperature decreases.

[0249] It should be noted that the purpose of the thermomechanical treatment in the preparation method of this invention is to integrate plastic deformation with heat treatment, thereby promoting changes in the microstructure of the material and improving its performance. Besides cold deformation followed by annealing, warm deformation refers to processing the material at a higher temperature, combining plastic deformation and annealing processes.

[0250] For example, Figure 20 This illustrates the warm-rolled Ti 50 Ni 50 Wide-temperature linear elasticity of strained glass alloys. Results show that, similar to strained glass alloys obtained by light annealing after cold rolling, the WR-83% and WR-92% samples also provide extremely stable linear stress-strain curves over a very wide temperature range from 93 K to 453 K, exhibiting both high strength and low hysteresis. Strengths reach as high as 1.5 GPa and 2 GPa, respectively, and they also possess larger recoverable strains of ~4.5%.

[0251] Besides rolling plastic deformation, cold drawing plastic deformation can achieve a greater degree of plastic deformation and ensures a smooth sample surface and no internal defects. Next, this paper selects Ti with the same composition... 50 Ni 50 The alloy was subjected to multiple rounds of room temperature cold drawing to obtain a sample with the ultimate cold drawing degree, and its cross-sectional area shrinkage rate reached 63%. This sample is simply referred to as CD-63% (Cold drawn-63%).

[0252] This invention is based on the following three understandings:

[0253] (1) After plastic deformation, the elastic limit and recovery strain of TiNi-based alloys can be improved by appropriate annealing treatment;

[0254] (2) Moderate annealing can not only eliminate Ti 50 Ni 50 The martensite produced by plastic deformation in the martensitic state of the alloy can maintain the degree of defects in the sample, keeping it in a strained glass state with a high defect concentration.

[0255] (3) The diameter of the cold-drawn wire sample is about 0.6 mm, which is smaller than that of the sheet material and is more sensitive to temperature;

[0256] The CD-63% sample was further annealed at 523 K for 3 min to achieve constant linear elasticity over a wide temperature range in cold-drawn wire.

[0257] Furthermore, Figure 21 This indicates Ti 50 Ni 50 The stress-strain curves of the CD-63% 523 K 3 min sample over a wide temperature range are shown. Similar to the rolled sample, this wire exhibits superior constant linear elasticity over a wide temperature range from 93 K to 453 K, achieving a strength of 2 GPa and providing an ultra-large recoverable strain of up to 6%. This indicates that the strained glass alloy possesses both high force field mobility and high temperature stability.

[0258] Furthermore, in another embodiment,

[0259] Figure 22 Figure (a) illustrates Ti induced by different processes. 50 Ni 50 Comparison of room temperature stress-strain in strained glass alloys. Results show:

[0260] (1) The degree of plastic deformation is positively correlated with the elastic limit of strain glass alloys. The greater the degree of plastic deformation, the higher the elastic limit. When the ultimate degree of plastic deformation is reached, the elastic limit can reach 2 GPa. Among them, the elastic limits of WR-83% and wire samples both reach the ideal strength range.

[0261] (2) Warm-rolled strain glass can provide greater recoverable strain than cold-rolled strain glass. This is because warm rolling can reduce the generation of non-transformable amorphous phases while inducing martensite into strain glass, thereby increasing the proportion of phase transformation phases in the sample and ultimately obtaining greater phase transformation strain.

[0262] (3) The cold drawing process will cause the wire sample to be oriented along the cold drawing direction. Therefore, the sample under this process has the largest recoverable strain, which is about 6%.

[0263] Furthermore, based on the wide-temperature-range tensile stress-strain curves, the Ti stress induced by different processes can be obtained. 50 Ni 50 The modulus-temperature dependence curves of strained glass alloys are shown in the figure. Figure 22 As shown in (b):

[0264] (1) For non-phase change spring steel structural materials, the elastic modulus will increase as the temperature decreases due to the strengthening of interatomic bonding force, exhibiting low temperature modulus hardening phenomenon.

[0265] (2) For CR-45% 573 K 15 s strain glass alloy with critical plastic deformation degree, the modulus softens due to phase transformation, and the modulus-temperature curve has a trough near the freezing temperature.

[0266] (3) For CR-80% 573 K 15 s, WR-83%, WR-92% and CD-63% 523 K 3 min strained glass alloys with higher plastic deformation, the elastic modulus fluctuates very little throughout the temperature range, that is, it has the Elinvar effect in a wide temperature range from 93 K to 453 K.

[0267] (4) Due to the difference between recovery strain and elastic limit, different Elinvar strained glass alloys have different elastic moduli, among which WR-83% and CD-63% 523 K 3 min strained glass alloys have ultra-low elastic moduli of ~33 GPa.

[0268] Based on the above embodiments and accompanying figures, this invention successfully prepared various high-strength, high-temperature Ti... 50 Ni 50 Strain-coated glass alloys (TiNi STG Elinvar alloys) exhibit the Elinvar effect across a wide temperature range of 93 K to 453 K. Specifically, the CR-80% sheet sample annealed at 573 K for 15 s provides 3.7% strain, 2 GPa strength, and 54 GPa modulus; the WR-83% and WR-92% sheet samples achieve 4.5% strain, 1.5 / 2 GPa strength, and 33 / 44 GPa modulus; while the CD-63% filament sample annealed at 523 K for 3 min exhibits the best Elinvar elasticity, providing a high strain of up to 6%, 2 GPa strength, and 33 GPa modulus.

[0269] like Figure 23 As shown in (a), the TiNi STG Elinvar alloy exhibits significant advantages in terms of recovery strain and elastic limit, outperforming not only previously reported Fe-based, Ti-based, and TiNi-based Elinvar alloys, but also surpassing classic "gum metal" (~2.3% strain and ~1.1 GPa strength), MgSc strained glass Elinvar alloy (1% strain and ~0.2 GPa strength), and the recently reported Co... 25 Ni 25 (HfTiZr) 50 High-entropy Elinvar alloy.

[0270] like Figure 23 As shown in (b), the TiNi STG Elinvar alloy can provide greater recovery strain, thus breaking the current trade-off between elastic limit and elastic modulus of Elinvar alloys. This alloy can maintain extremely high strength while having a low elastic modulus.

[0271] Furthermore, for nonlinear elastic materials, their elastic energy storage density U e The area under the unloading curve in the stress-strain curve is U, while the area between the loading and unloading curves is the elastic energy loss U. loss It is commonly used to measure the heat dissipation caused by internal friction in a material during a stress-strain cycle. Due to the linear elasticity U provided by TiNi STG Elinvar alloy... loss It is extremely low, therefore its energy efficiency is extremely high, close to 100%.

[0272] See Figure 24 The figure illustrates a comparison of the elastic energy storage density of the TiNi STG Elinvar alloy with existing Elinvar alloys and classic linear elastic alloys. As shown in the figure, the elastic energy storage density U of the TiNi STG Elinvar alloy... e All exceeded 30 J / cm 3 Thanks to its high strength of 2 GPa and large recoverable strain of 6%, the CD-63% annealed sample at 523 K for 3 min exhibits the highest elastic storage density U. e ~ 61 J / cm 3 Furthermore, the elastic energy storage density of the TiNi STG Elinvar alloy not only exceeds that of existing Elinvar alloys, including Fe-based, Ti-based "gum" metals, MgSc strained glass Elinvar alloys, and Co... 25 Ni 25 (HfTiZr) 50 High-entropy Elinvar alloys, and even higher than classic linear elastic alloys, including NICSMA and Ti. 49.2 Ni 50.8 STG, Nb nanowire-reinforced TiNi alloys, and classic industrial steel, titanium, magnesium, and aluminum alloys.

[0273] Figure 25 The diagram illustrates the elastic energy storage-temperature dependence curves of the TiNi STG Elinvar alloy and the existing Elinvar alloy. As the temperature decreases, the elastic energy storage density of spring steel gradually increases, while the TiNi STG Elinvar alloy not only provides several times the elastic energy storage density of spring steel but also maintains stability over a wide temperature range of 93 K to 453 K, which is superior to the existing Elinvar alloy. Furthermore, the TiNi STG Elinvar alloy provides stable, high elastic energy storage over a wide temperature range, sufficient to cover extreme temperature conditions in locations such as the Moon, Mars, and space stations, indicating broad application prospects for this invention.

[0274] Figure 26This illustrates a comparison of TiNi STG Elinvar alloy and different energy storage types in terms of energy density per unit mass and operating temperature range. The results show that traditional energy storage methods, including fuel cells, chemical cells, flywheel mechanical energy storage, supercapacitors, and capacitors, are difficult to achieve energy storage and release in low-temperature environments because their operating principles are based on chemical reactions or charge movement. However, TiNi STG Elinvar alloy elastic energy storage not only possesses energy density comparable to supercapacitors but also effectively compensates for the shortcomings of current energy storage forms in low-temperature applications.

[0275] Figure 27 The figure illustrates a comparison of the energy density and power density per unit mass or unit volume of TiNi STG Elinvar alloy with different energy storage types, where the diagonal lines correspond to different release times. As shown in the figure, there is a trade-off between energy density and power density for different types of energy storage. For example, while fuel cells can provide enormous chemical energy storage, they have long release times and low power density. In contrast, TiNi STG Elinvar alloy not only possesses elastic energy storage capacity comparable to supercapacitors but also exhibits extremely high power density and ultra-short release times. These superior characteristics enable this alloy to well meet the stringent requirements of energy storage systems in terms of compact structure, large-capacity energy storage, high-power drive, and rapid response.

[0276] The above description has been given for purposes of illustration and description. Furthermore, this description is not intended to limit the embodiments of the invention to the forms disclosed herein. Although numerous exemplary aspects and embodiments have been discussed above, those skilled in the art will recognize certain variations, modifications, alterations, additions, and sub-combinations therein.

Claims

1. A method for preparing a strain-coated glass alloy, characterized in that, Includes the following steps: Thermomechanical treatment of TiNi-based alloys exhibiting martensitic phase transformation characteristics can suppress the martensitic phase transformation and form a strained glassy state. The thermomechanical treatment combines plastic deformation with heat treatment. By adjusting the degree of plastic deformation and heat treatment parameters, the concentration of material defects is controlled, transforming TiNi-based alloy materials into TiNi-based strain glass alloys.

2. The preparation method according to claim 1, characterized in that, Preferred, The degree of plastic deformation is not less than the critical degree of plastic deformation required to completely suppress the martensitic phase transformation; and The heat treatment parameters are controlled within a range that maintains the material in a strained glass state with a high defect concentration.

3. The preparation method according to claim 1, characterized in that, The thermomechanical treatment is selected from one of the following methods: 1) Annealing after cold plastic deformation: First, perform cold plastic deformation at room temperature, then perform annealing; or 2) Warm plastic deformation treatment: at temperatures above alloy A f Plastic deformation occurs at a temperature where A... f The temperature indicates the termination temperature of the stabilization martensite reversal transformation.

4. The preparation method according to claim 1, characterized in that, The TiNi-based alloy material is in the form of a plate or wire.

5. The preparation method according to claim 4, characterized in that, When the plate or wire is subjected to thermomechanical treatment, The plastic deformation is at least one of cold rolling, warm rolling, or cold drawing, wherein... When cold rolling or cold drawing, the heat treatment also includes annealing. During warm rolling, the degree of plastic deformation is adjusted; or during cold rolling, the degree of plastic deformation, annealing temperature, and annealing time are adjusted to control the defect concentration, phase transformation behavior, and mechanical properties of the TiNi-based alloy material, so that it exhibits the constant elasticity Elinvar effect over a wide temperature range.

6. The preparation method according to claim 5, characterized in that, The deformation degree of cold rolling is 30% to 85%, the deformation degree of warm rolling is 60% to 93%, and the cross-sectional area shrinkage rate of cold drawing is 50% to 65%, preferably 63%.

7. The preparation method according to claim 5, characterized in that, 1) When the TiNi-based alloy material is Ti 39 Ni 41 Nb 20 For alloy sheets, the parameters for annealing after cold rolling are as follows: Annealing temperature range: 723 K - 823 K; Annealing time range: 5 min - 60 min; 2) When the TiNi-based alloy material is Ti 50 Ni 50 For alloy sheets, the parameters for annealing after cold rolling are as follows: Annealing temperature: 523K to 583K; Annealing time: Short annealing time not exceeding 3 minutes; 3) When the TiNi-based alloy material is Ti 50 Ni 50 For alloy wire, the parameters for annealing after cold drawing are as follows: Annealing temperature: 473K to 573K; Annealing time: Short annealing time not exceeding 15 minutes.

8. The preparation method according to claim 5, characterized in that, The temperature range is 93 K to 453 K.

9. The preparation method according to claim 1, characterized in that, The elastic limit properties of the TiNi-based strained glass alloy are: strength of 1.5 GPa-2 GPa and recoverable strain of 4.5%-6%. The elastic modulus of the TiNi-based strained glass alloy is 33 GPa-54 GPa; The elastic energy storage density of the TiNi-based strained glass alloy is 30 J / cm³. 3 -61J / cm 3 .

10. The preparation method according to claim 4, characterized in that, Before thermomechanical treatment, the TiNi-based alloy material plates also undergo the following treatments: The initial sheet metal is processed into metal strips using wire electrical discharge machining, followed by mechanical polishing. The mechanically polished sample was placed in a quartz tube and sealed, and then subjected to solid solution treatment under argon protection. After solution treatment, mechanical polishing is performed again.